Sosialisasi Produk dan Pengelolaan Keuangan Usaha Mikro Kue Tradisional “Puji Lestari“ di Menur Pumpungan Kota Surabaya - Mataji Mataji; Sigit Santoso (Lembaga Pengembangan Kinerja Dosen, 2025)
Since the implementation of the ASEAN Economic Community (AEC) at the end of 2015, all economic actors—including SMEs and microenterprises—are expected to improve and adapt in order to enhance the quality of both goods and services. Failure to do so may result in Indonesia becoming a